The imposters : a novel - Rachman, Tom (Little, Brown and Company, 2023)
Determined to finish her final book and reverse her fortunes before her mind goes, Dora Frenhofer uses fascinating real characters from her own life, including her missing brother, her estranged daughter, her erstwhile lover, and her last remaining friend, that results in an unforeseen twist.